School Stress and Parental Bonding in Colombian Adolescents During Covid-19; [Estrés Escolar y Estilos Parentales en Adolescentes Colombianos Durante el Covid-19] - Rojas-Andrade, R (Revista Latinoamericana de Ciencias Sociales, 2024)
To examine differences in school stress based on perceived parental style among Colombian stu-dents, the Parental Bonding Instrument and a school stress index were administered to 1287 adoles-cents from the department of Caldas, Colombia. The analysis revealed that 35.1% of participants exhibited excessive academic concern. Regarding the perception of parental style, 31.6% reported receiving optimal parenting, 14.1% reported affectionate restraint, 26.5% parenting with control wit-hout affection, and 27.7% described neglectful parenting. The results indicated a significant correla-tion between school stress and parental control, as well as a significant negative correlation with af-fection. Parental styles that appropriately balance affection and control were associated with lower school stress responses, suggesting the importance of promoting balanced parenting practices to improve the academic well-being of adolescents. © 2024 Revista Latinoamericana de Ciencias Sociales. All rights reserved.